Microscopic Study of Dopant Distribution in Europium Doped SrGa2S4: Impact on Thermal Quenching and Phosphor Performance. (15th September 2017) - Martin, Lisa I. D. J.; Poelman, Dirk; Smet, Philippe F.; Joos, Jonas J.
Abstract : White light emitting diodes start to dominate lighting and display applications. However, the properties of the phosphors used in these devices strongly depend on synthesis conditions. A better understanding of how performance-determining mechanisms such as thermal quenching are influenced by synthesis conditions and sample composition is necessary to achieve the required standards in a goal-oriented strategy. In this paper, a microscopic thermal quenching study on green-emitting SrGa2 S4 :Eu 2+ phosphors by means of cathodoluminescence spectroscopy and energy dispersive X-ray analysis in a scanning electron microscope is used to extend our knowledge beyond averaged information obtained on bulk material. Elemental and cathodoluminescence mapping at different temperatures made it possible to determine thermal quenching profiles for sub-micrometer sized areas. These revealed a broad range of local quenching temperatures for samples with ill-distributed dopant ions. For the associated activation energy an upper limit of 0.61 eV was identified, corresponding to the intrinsic thermal quenching of isolated europium ions. Furthermore, the results confirm a previously suggested thermal quenching model which involves the presence of both isolated and clustered dopant ions.